Social Competence of Islamic Religious Education Teachers in Shaping the Honest Character of Elementary School Students - Syamsuriani; Muhammad Naim; M Nasri Hamang; Rosmiati Ramli (CV. Edujavare Publishing, 2026)
This study is grounded in the persistence of dishonest behavior among elementary school students, such as cheating, concealing mistakes, and manipulating information, while the social interaction of Islamic Religious Education (PAI) teachers has not been fully dialogic, empathetic, and well directed. This study aims to describe the level of PAI teachers' social competence, analyze the process of shaping students' honest character, identify supporting and inhibiting factors, and formulate the role of PAI teachers' social competence in shaping students' honest character at SDN 002 North Bontang. This research employs a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with the principal, homeroom teachers, PAI teachers, and fourth-to-sixth grade students, as well as documentation study. Data were analyzed through data reduction, data display, and conclusion drawing, with validity tested through credibility, transferability, dependability, and confirmability. The findings show that PAI teachers' social competence is reflected in five dimensions: communicative, collaborative, adaptive, participatory, and relational abilities. These dimensions significantly contribute to shaping students' honesty in speech, action, learning, trustworthiness, and awareness of divine supervision. The main supporting factors include teacher role modeling, principal support, parental collaboration, and students' spiritual awareness, while inhibiting factors include limited time, peer influence, and digital-era challenges. This study affirms that strengthening honest character requires sustained synergy among schools, teachers, and families.